Fotofísica e determinação de parâmetros fotodinâmicos da ftalocianina de zinco em meios homogêneo e microheterogêneo - Ribeiro, Juliana (2003)
In the present work, the influence of the homogeneous and microheterogeneous media on the photophysics of Zinc Phthalocyanine (ZnPc) was evaluated, aiming to contributo for a better understanding on the influence of médium on the electronic structure of this compound. The dependence between the fluorescense quantum yield (Of), in the different media studied, and the polarity scale Et(30), was evaluated. This analysis showed a direct ratio between Of and the médium polarity, which may be related to the increase in the energy difference between the Si (nw*) e S2 (n,n*) States. Despite the low values of Of, the increase of this parameter with the polarity is higher in protic solvents, indicating that more specific polar interactions added to the typical interactions of non-protic solvents is decisive to give the observed trend. The Of in Sodium Dodecyl Sulphate (SDS) follows the same trend observed for protic solvents. On the other hand, the value measured in Cetyl Trimethyl Ammonium Bromide (CTAB) (Of = 0,002) is extremely low. Experimental evidences indicate that this must be due to the action of bromide ions, which potentializes the spin orbit coupling. Measurements of quantum yield of singlet oxygen generation (Oa) has been made in steady-state regimen in different media, through the degradation control of the compound 1,3-Diphenylisobenzofurane (DPBF). The results show to be coherent with the values reported in literature. However, the O a measured in Dimetylsufoxide (DMSO) revealed to be divergent. On the other hand, measures of OA made in the same solvent using time resolved technique, furnished results which agree with the value estimated by steady-state measurements. The values estimated in chloroform (CHCI3) and carbon tetrachloride14 (CCLt) were anomalously high, very probably due to the extremely long singlet oxygen lifetimes in these solvents. The Photodynamic Activity (PA) also was measured in different media. The results suggest that a PA is a parameter capable to quantify the reactivity of a photosensitizer not only in terms of its capacity of generation of singlet oxygen ('Oj), but also of other oxygen active species. The value measured for the PA of ZnPc in SDS (42 ± 2 m2/Ws) agrees very well to the previously obtained using uric acid (UA) (49 ± 3 m2/Ws). The value of the PA of ZnPc in CTAB is lower to the obtained in SDS which must be related to the physical quenching promoted by the structure of the CTAB. The value of the PA of ZnPc in SDS reveals, that apparently this dye is at least two times more efficient than Photofrin II or Methylene Blue. Considering that the molar absorptivity of ZnPc is around 102 times higher than the value for Photofrin H, the photodynamic action ofZnPc is at least 200 times higher than the former.